Analisis Metode Penelitian pada Skripsi Mahasiswa Prodi Pendidikan Agama Islam - Mukhid, Abd (LP2M IAI Miftahul Ulum Pamekasan, 2021)
This research aims to determine errors in preparing research methods carried out by students of the Islamic Religious Education study program in 2015, 2016 and 2017 STAIN Pamekasan as well as efforts to correct these errors. This research uses a library approach with data analysis using content analysis. The research results show that errors that occur are generally made in aspects of elements that require detailed actions such as determining the reasons for choosing a research location, determining data sources, determining research instruments, and determining data validity tests. Meanwhile, several improvements that can be made as a solution to errors in research methods in the thesis are paying more attention to the systematic preparation of STAIN Pamekasan scientific papers, especially in the parts that require detailed reasons such as determining the reasons for choosing the research location correctly; primary and secondary data sources correctly; research instruments used to test validity and reliability; test the validity of the data clearly; and documents you want to collect in detail.